PERAN TENAGA PENDAMPING PROFESIONAL DI KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Isma Ardayani; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Government of the Republic of Indonesia has made the village a fulcrum in enhancing national development through the third nawa cita, namely developing Indonesia from the periphery by strengthening regions and villages, one of whose agendas is to oversee the implementation of Law no. 6 of 2014 concerning Villages. The lack of human resource capacity in the village has resulted in an insignificant increase in the development and empowerment of village communities, therefore as a reference, the Government issued a policy in the form of Permendesa PDTT No. 18 of 2019 concerning general guidelines for assisting village communities. To carry out village community assistance, the government is assisted by professional assistants who have qualifications and competence in the field of assistance and empowerment of village communities. This study aims to analyze the role of professional assistants in Rambah sub-district, Rokan Hulu district, and to analyze what are the obstacles faced by professional assistants in carrying out their role. This study uses a qualitative method Participatory Rural Apricial (PRA) by using an inductive mindset that produces descriptive data. Data collection techniques were carried out in triangulation, namely a combination of observation, interviews, and documentation. The results showed that The Role of Professional Assistants in Rambah District, Rokan Hulu Regency was good, however, there were still some obstacles that occurred such as a lack of quality human resources, local village assistants who were not optimal in carrying out their roles, professional assistants who did not have advice and infrastructure, and limited budget. Keywords: Professional Assistants, Community Empowerment, village community assistance